Electrolyte and lithium ion battery
By adding n-butyl isocyanate acetate silane compound and glyoxal disulfate to the lithium-ion battery electrolyte solution, a dense passivation film and solid electrolyte film are generated, which solves the problem of poor circulation stability of lithium-ion batteries in silicon carbon negative electrode system. The cycle stability and capacity retention rate of the battery are significantly improved.
Patent Information
- Application Number
- CN202411344971.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The cycle stability of the lithium-ion battery of silicon carbon anode system is poor, mainly due to the pulverization and SEI film rupture caused by volume expansion and contraction of silicon particles during the deintercalation of lithium ions, which in turn causes the electrolyte to continue to react and consume.
Adding isocyanate n-butyl acetate silane compounds and glyoxal disulfate to the electrolyte, the n-butyl acetate silane compounds preferentially form a dense and stable passivation film on the silicon carbon negative electrode to reduce the reaction on the negative electrode surface It can be used to generate a solid electrolyte membrane with good ionic conductivity through Si-O bond polymerization, which inhibits the electrolyte consumption caused by the expansion of silicon particles, and at the same time, glyoxal disulfate reduces the interface impedance of the SEI membrane.
The cycle stability of the lithium-ion battery in silicon-carbon negative electrode system is improved, the interface impedance is reduced, the cycle life of the battery and the first-effect capacity retention rate are extended, and the internal resistance and thickness of the battery are reduced.
Smart Images

Figure BDA0005060709970000022 
Figure BDA0005060709970000052 
Figure BDA0005060709970000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have become an indispensable source of power in the fields of automobiles, 3C electronics, engineering machinery, aerospace, etc. due to their high operating voltage, no memory effect, long cycle life and environmental friendliness. The electrolyte is called the "blood" of lithium-ion batteries. It is usually composed of lithium salts, solvents and additives. The electrolyte has an important influence on the cycle performance, rate performance and safety performance of lithium-ion batteries.
[0003] Silicon-carbon negative electrode materials have high capacity, making them the first choice for negative electrode materials of next-generation high-energy-density lithium batteries. However, there are also many problems with silicon-carbon negative electrode materials. For example, silicon particles expand and shrink in volume during lithium ion insertion and extraction, which leads to pulverization and shedding of silicon particles and rupture of SEI membrane, which in turn causes continuous reaction and consumption of electrolyte, resulting in poor cycle performance of lithium batteries using silicon-carbon negative electrode materials. Therefore, there is an urgent need for a method to solve the problem of poor cycle performance of silicon-carbon negative electrode batteries. Summary of the invention
[0004] The main purpose of the present invention is to provide an electrolyte and a lithium ion battery to solve the problem of poor cycle stability of lithium ion batteries with silicon-carbon negative electrode system in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, an electrolyte is provided, which comprises, by weight, 8 to 15 parts of a lithium salt, 10 to 90 parts of an organic solvent, 0.3 to 3 parts of an isocyanate acetate n-butyl silane compound and 0.05 to 0.3 parts of glyoxal disulfate.
[0006] Furthermore, the electrolyte includes 12 to 14 parts of lithium salt, 70 to 90 parts of organic solvent, 0.5 to 3 parts of isocyanate acetate n-butyl silane compound and 0.05 to 0.2 parts of glyoxal disulfate.
[0007] Furthermore, the mass ratio of the above-mentioned isocyanate acetate n-butyl silane compound to glyoxal disulfate is 1:0.016-0.1.
[0008] Furthermore, the structure of the above-mentioned isocyanate acetate n-butyl silane compound is wherein n is an integer, 1≤n≤10; and / or, R1, R2 and R3 are each independently selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10Alkoxy, substituted or unsubstituted C2~C 10 Alkynyl, substituted or unsubstituted C6~C 12 any one of aryl, (R4)3SiO-, R4 is selected from substituted or unsubstituted C1~C 10 Any one of the alkyl groups.
[0009] Furthermore, the above R1, R2 and R3 are each independently selected from substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C4 alkoxy, substituted or unsubstituted C2-C5 alkynyl, substituted or unsubstituted C6-C8 aryl, (R4)3SiO - Any one of the following, wherein R4 is selected from any one of substituted or unsubstituted C1-C3 alkyl groups.
[0010] Furthermore, the above R1, R2 and R3 are each independently selected from methyl, ethyl, methoxy, ethoxy, ethynyl, phenyl, (CH3)3SiO - 、(CH3CH2)3SiO - Any one of .
[0011] Furthermore, the above-mentioned isocyanate acetate n-butyl silane compound is selected from
[0012] Any one or more of .
[0014] Furthermore, the organic solvent is selected from organic carbonate compounds, ionic liquids, alkylene ether compounds, aromatic ether compounds, C 1-10 Any one or more of alkyl ether compounds, cyclic ether compounds, carboxylate compounds, sulfone compounds, and nitrile compounds; preferably, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, 1,4-butyrolactone, ethyl methyl carbonate, methyl propionate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, dimethyl ether, phenylene sulfide, acetonitrile, glutaronitrile, and cyclopentane sulfone; further, the organic solvent is preferably a combination of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate, and the mass ratio of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is 15-25:35-45:35-45.
[0015] Furthermore, the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium nitrate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalate)phosphate and lithium tetrafluoro(oxalate)phosphate; preferably, the lithium salt is lithium hexafluorophosphate.
[0016] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte, a separator and a silicon-carbon negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte.
[0017] Applying the technical solution of the present application, adding isocyanate acetate n-butyl silane compounds to the electrolyte of the present application helps to enable isocyanate acetate n-butyl silane compounds to preferentially form a dense and stable passivation film on the silicon-carbon negative electrode, thereby helping to reduce the reactivity of the negative electrode surface to inhibit the occurrence of electrolyte side reactions; the Si-O bond in the isocyanate acetate n-butyl silane compound has the characteristics of high bond energy, thereby helping to make the isocyanate in the isocyanate acetate n-butyl silane compound undergo polymerization to generate a similar polymer solid electrolyte membrane, which has good ionic conductivity, strong flexibility and stability, and can inhibit the continuous consumption of electrolyte caused by the expansion of silicon particles during the cycle, reduce the interface impedance, and then help to improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. Adding glyoxal disulfate to the electrolyte of the present application helps to reduce the interface impedance of the dense SEI film formed by the isocyanate acetate n-butyl silane compound in the electrolyte, thereby helping to further improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. It is preferred to control the composition and weight fraction of the electrolyte within the above range, which helps to give full play to the synergistic effect between the components and promote the formation of the passivation film, thereby helping to further improve the cycle stability of the lithium-ion battery with a silicon-carbon negative electrode system. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As analyzed in the background technology of the present application, lithium-ion batteries with silicon-carbon negative electrode systems in the prior art have the problem of poor cycle stability. In order to solve this problem, the present application provides an electrolyte and a lithium-ion battery.
[0020] In a typical embodiment of the present application, an electrolyte is provided, which includes, by weight, 8 to 15 parts of a lithium salt, 10 to 90 parts of an organic solvent, 0.3 to 3 parts of an isocyanate acetate n-butyl silane compound, and 0.05 to 0.3 parts of glyoxal disulfate.
[0021] Adding isocyanate acetate n-butyl silane compounds in the electrolyte of the present application helps to make isocyanate acetate n-butyl silane compounds preferentially generate a dense and stable passivation film on the silicon-carbon negative electrode, thereby helping to reduce the reactivity of the negative electrode surface to inhibit the occurrence of electrolyte side reactions; the Si-O bond in the isocyanate acetate n-butyl silane compounds has the characteristics of high bond energy, thereby helping to make the isocyanate in the isocyanate acetate n-butyl silane compounds undergo polymerization to generate a similar polymer solid electrolyte membrane, which has good ionic conductivity, strong flexibility and stability, and can inhibit the continuous consumption of electrolyte caused by the expansion of silicon particles during the cycle, reduce the interface impedance, and then help to improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. Adding glyoxal disulfate in the electrolyte of the present application helps to reduce the interface impedance of the dense SEI film formed by the isocyanate acetate n-butyl silane compounds in the electrolyte, thereby helping to further improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. It is preferred to control the composition and weight fraction of the electrolyte within the above range, which helps to give full play to the synergistic effect between the components and promote the formation of the passivation film, thereby helping to further improve the cycle stability of the lithium-ion battery with a silicon-carbon negative electrode system.
[0022] In order to further improve the cycle stability of lithium-ion batteries with silicon-carbon negative electrode systems, in one embodiment of the present application, the electrolyte preferably includes 12 to 14 parts of lithium salt, 70 to 90 parts of organic solvent, 0.5 to 3 parts of isocyanate acetate n-butyl silane compounds and 0.05 to 0.2 parts of glyoxal disulfate.
[0023] In one embodiment of the present application, the mass ratio of the above-mentioned isocyanate acetate n-butyl silane compound to glyoxal disulfate is 1:0.016-0.1.
[0024] It is preferred to control the mass ratio of isocyanate acetate n-butyl silane compounds to glyoxal disulfate within the above range, which helps to further reduce the interfacial impedance of the dense SEI film formed by the isocyanate acetate n-butyl silane compounds in the electrolyte, thereby helping to further improve the cycle stability of lithium-ion batteries with silicon-carbon negative electrode systems.
[0025] In one embodiment of the present application, the structure of the above-mentioned isocyanate acetate n-butyl silane compound is wherein n is an integer, 1≤n≤10; and / or, R1, R2 and R3 are each independently selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Alkoxy, substituted or unsubstituted C2~C 10Alkynyl, substituted or unsubstituted C6~C 12 any one of alkylaryl, (R4)3SiO-, R4 is selected from substituted or unsubstituted C1~C 10 Any one of the alkyl groups.
[0026] In order to further improve the cycle stability of the silicon-carbon negative electrode system lithium-ion battery, in one embodiment of the present application, it is preferred that the above R1, R2 and R3 are each independently selected from substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C4 alkoxy, substituted or unsubstituted C2-C5 alkynyl, substituted or unsubstituted C6-C8 alkylaryl, (R4)3SiO - Any one of the following, wherein R4 is selected from any one of substituted or unsubstituted C1-C3 alkyl groups.
[0027] In order to further improve the cycle stability of the lithium-ion battery with silicon-carbon negative electrode system, in one embodiment of the present application, it is preferred that the above R1, R2 and R3 are each independently selected from methyl, ethyl, methoxy, ethoxy, ethynyl, phenyl, (CH3)3SiO - 、(CH3CH2)3SiO - Any one of .
[0028] In order to further improve the cycle stability of the lithium-ion battery with silicon-carbon negative electrode system, in one embodiment of the present application, the above-mentioned isocyanate acetate n-butyl silane compound is preferably selected from Any one or more of .
[0030] In one embodiment of the present application, the organic solvent is selected from organic carbonate compounds, ionic liquids, alkylene ether compounds, aromatic ether compounds, C 1-10 Any one or more of alkyl ether compounds, cyclic ether compounds, carboxylate compounds, sulfone compounds, and nitrile compounds; preferably, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, 1,4-butyrolactone, ethyl methyl carbonate, methyl propionate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, dimethyl ether, phenylene sulfide, acetonitrile, glutaronitrile, and cyclopentane sulfone; further, the organic solvent is preferably a combination of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate, and the mass ratio of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is 15-25:35-45:35-45.
[0031] It is preferred to control the type of organic solvent within the above range, which helps to improve the solubility of lithium salt, isocyanate acetate n-butyl silane compound and glyoxal disulfate in the organic solvent, thereby helping to improve the stability of the electrolyte.
[0032] In one embodiment of the present application, the above-mentioned lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium nitrate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalate)phosphate and lithium tetrafluoro(oxalate)phosphate; preferably, the lithium salt is lithium hexafluorophosphate.
[0033] It is preferred to control the type of lithium salt within the above range, which helps to further improve the ion transfer rate of the electrolyte and the stability of the electrolyte.
[0034] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte, a separator and a silicon-carbon negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte.
[0035] Since the electrolyte in the above lithium-ion battery is the electrolyte of the present application, the lithium-ion battery has excellent cycle stability.
[0036] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0037] Example 1
[0038] Preparation of electrolyte
[0039] In a glove box filled with argon (oxygen <0.1ppm, water <0.1ppm), ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a mass ratio of 20:40:40 to obtain an organic solvent. In parts by weight, 13 parts of lithium hexafluorophosphate were slowly added to 86.45 parts of the organic solvent. After complete dissolution, 0.5 parts of additive 1 and 0.05 parts of glyoxal disulfate were added. After complete dissolution, the electrolyte was uniformly stirred to obtain an electrolyte. The structural formula of additive 1 is
[0040] Preparation of cathode materials
[0041] Mix 92% NCM811, 3% conductive agent SP, 2% single-walled carbon nanotubes, and 3% binder PVDF in a mass ratio, add solvent N-methylpyrrolidone and stir to form a uniform slurry, apply it on a 12-micron thick aluminum foil, roll and cut it to obtain the positive electrode material
[0042] Preparation of negative electrode materials
[0043] 85% silicon carbon, 10% single-walled carbon nanotubes and 5% binder SBR in a mass ratio were mixed evenly, and deionized water was added as a solvent. The slurry was then coated on an 8-micron copper foil, dried, rolled and cut to obtain a negative electrode material.
[0044] Preparation of batteries
[0045] In a dry environment with a dew point controlled below -60°C, the positive electrode sheet, separator, and negative electrode sheet are stacked in order to ensure that the separator completely separates the positive electrode sheet from the negative electrode sheet, and the negative electrode completely covers the positive electrode. The battery cells are made by stacking the sheets, and then packaged in an aluminum-plastic film with glue ears after hot pressing. After baking until the moisture content is qualified, the prepared electrolyte is injected into the soft-pack battery cell, followed by sealing, formation, secondary sealing aging, and capacity division to obtain an experimental battery for testing.
[0046] Example 2
[0047] The difference from Example 1 is that the weight portion of additive 1 is 1 part, and an experimental battery is finally obtained.
[0048] Example 3
[0049] The difference from Example 1 is that the weight portion of the additive 1 is 2 parts, and an experimental battery is finally obtained.
[0050] Example 4
[0051] The difference from Example 1 is that the weight portion of the additive 1 is 3 parts, and an experimental battery is finally obtained.
[0052] Example 5
[0053] The difference from Example 1 is that the weight portion of the additive 1 is 1 part, the weight portion of glyoxal disulfate is 0.1 part, and finally an experimental battery is obtained.
[0054] Example 6
[0055] The difference from Example 1 is that the weight portion of glyoxal disulfate is 0.1 parts, and an experimental battery is finally obtained.
[0056] Example 7
[0057] The difference from Example 1 is that the weight portion of glyoxal disulfate is 0.2 parts, and an experimental battery is finally obtained.
[0058] Example 8
[0059] The difference from Example 1 is that the weight portion of the additive 1 is 1 part, the weight portion of glyoxal disulfate is 0.2 parts, and finally an experimental battery is obtained.
[0060] Example 9
[0061] The difference from Example 1 is that the weight portion of the additive 1 is 0.3 parts, the weight portion of glyoxal disulfate is 0.3 parts, and finally an experimental battery is obtained.
[0062] Example 10
[0063] The difference from Example 1 is that By replacing additive 1, an experimental battery was finally obtained.
[0064] Embodiment 11
[0065] The difference from Example 1 is that By replacing additive 1, an experimental battery was finally obtained.
[0066] Example 12
[0067] The difference from Example 1 is that By replacing additive 1, an experimental battery was finally obtained.
[0068] Example 13
[0069] The difference from Example 1 is that the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 25:35:35, and an experimental battery is finally obtained.
[0070] Embodiment 14
[0071] The difference from Example 1 is that the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 15:45:45, and an experimental battery is finally obtained.
[0072] Embodiment 15
[0073] The difference from Example 1 is that the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 10:50:50, and an experimental battery is finally obtained.
[0074] Comparative Example 1
[0075] The difference from Example 1 is that 2 parts of vinyl sulfate (VC) are used to replace 0.5 parts of Additive 1 and 0.05 parts of glyoxal disulfate, and finally an experimental battery is obtained.
[0076] Comparative Example 2
[0077] The difference from Example 1 is that 0.5 parts of Additive 1 and 0.05 parts of glyoxal disulfate are replaced by 1 part of fluoroethylene carbonate (FEC), and finally an experimental battery is obtained.
[0078] Comparative Example 3
[0079] The difference from Example 1 is that 0.5 parts of Additive 1 and 0.05 parts of glyoxal disulfate are replaced by 1 part of ethylene sulfate (DTD), and finally an experimental battery is obtained.
[0080] Comparative Example 4
[0081] The difference from Example 1 is that the weight portion of the additive 1 is 1 part, and glyoxal disulfate is not added, and finally an experimental battery is obtained.
[0082] Electrical performance test
[0083] After soaking the above soft-pack battery for 24 hours, use a battery test cabinet to form and divide the capacity. The formation process is 0.02C constant current charging to 3.2V, 0.1C constant current charging to 3.7V; aging and shelving at 45°C for 24 hours; the capacity division process is 0.1C constant current and constant voltage charging to 4.25V, the end current is 0.05C, 0.1C constant current discharge to 2.75V, 0.33C constant current and constant voltage charging to 4.25V, the end current is 0.05C, and 0.33C constant current discharge to 2.75V. The battery after capacity division is charged and discharged at 1C / 1C constant current and constant voltage for 800 cycles, and the voltage range is set to 2.75-4.25V. After the cycle is completed, the impedance of the battery is tested with an internal resistance meter, and the thickness of the battery is tested with a vernier caliper. The internal resistance growth rate is equal to the difference before and after the cycle divided by the internal resistance of the battery before the cycle, and the thickness growth rate is equal to the difference before and after the cycle divided by the thickness of the battery before the cycle. Comparing the internal resistance growth rate and thickness growth rate of the battery, the specific results are shown in Table 1.
[0084] Table 1
[0085]
[0086]
[0087] By comparing the results of the embodiments and the comparative examples, it can be seen that the electrolyte to which the additives of isocyanate acetate n-butyl silane compound and glyoxal disulfate provided by the present invention are added significantly improves the initial efficiency and capacity retention rate after cycle in the test of soft-pack batteries, reduces the increase in cycle internal resistance and battery thickness, and suppresses the impedance growth caused by the reaction of the electrolyte with the lithiated silicon negative electrode during the cycle by protecting the silicon negative electrode from particle breakage caused by repeated lithium insertion and extraction and reducing the interface impedance to a certain extent, thereby improving the cycle stability of the battery.
[0088] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0089] Adding isocyanate acetate n-butyl silane compounds in the electrolyte of the present application helps to make isocyanate acetate n-butyl silane compounds preferentially generate a dense and stable passivation film on the silicon-carbon negative electrode, thereby helping to reduce the reactivity of the negative electrode surface to inhibit the occurrence of electrolyte side reactions; the Si-O bond in the isocyanate acetate n-butyl silane compounds has the characteristics of high bond energy, thereby helping to make the isocyanate in the isocyanate acetate n-butyl silane compounds undergo polymerization to generate a similar polymer solid electrolyte membrane, which has good ionic conductivity, strong flexibility and stability, and can inhibit the continuous consumption of electrolyte caused by the expansion of silicon particles during the cycle, reduce the interface impedance, and then help to improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. Adding glyoxal disulfate in the electrolyte of the present application helps to reduce the interface impedance of the dense SEI film formed by the isocyanate acetate n-butyl silane compounds in the electrolyte, thereby helping to further improve the cycle stability of the lithium-ion battery of the silicon-carbon negative electrode system. It is preferred to control the composition and weight fraction of the electrolyte within the above range, which helps to give full play to the synergistic effect between the components and promote the formation of the passivation film, thereby helping to further improve the cycle stability of the lithium-ion battery with a silicon-carbon negative electrode system.
[0090] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: In parts by weight, the electrolyte comprises: 8 to 15 parts of lithium salt; 10 to 90 parts of an organic solvent; 0.3 to 3 parts of isocyanate acetate n-butyl silane compound; and 0.05 to 0.3 parts of glyoxal disulfate.
2. The electrolyte according to claim 1, characterized in that The electrolyte comprises: 12 to 14 parts of lithium salt; 70-90 parts of an organic solvent; 0.5 to 3 parts of isocyanate acetate n-butyl silane compound; and 0.05 to 0.2 parts of glyoxal disulfate.
3. The electrolyte according to claim 1 or 2, characterized in that The mass ratio of the isocyanate acetate n-butyl silane compound to the glyoxal disulfate is 1:0.016-0.
1.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The structure of the isocyanate acetate n-butyl silane compound is: wherein n is an integer, 1≤n≤10; and / or, R1, R2 and R3 are each independently selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Alkoxy, substituted or unsubstituted C2~C 10 Alkynyl, substituted or unsubstituted C6~C 12 any one of aryl, (R4)3SiO-, R4 is selected from substituted or unsubstituted C1~C 10 Any one of the alkyl groups.
5. The electrolyte according to claim 4, characterized in that The R1, R2 and R3 are each independently selected from substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C4 alkoxy, substituted or unsubstituted C2-C5 alkynyl, substituted or unsubstituted C6-C8 aryl, (R4)3SiO - Any one of the following, wherein R4 is selected from any one of substituted or unsubstituted C1-C3 alkyl groups.
6. The electrolyte according to claim 5, characterized in that The R1, R2 and R3 are each independently selected from methyl, ethyl, methoxy, ethoxy, ethynyl, phenyl, (CH3)3SiO - 、(CH3CH2)3SiO - Any one of .
7. The electrolyte according to claim 6, characterized in that The isocyanate acetate n-butyl silane compound is selected from Any one or more of .
8. The electrolyte according to any one of claims 1 to 7, characterized in that The organic solvent is selected from organic carbonate compounds, ionic liquids, alkylene ether compounds, aromatic ether compounds, C 1-10 Any one or more of alkyl ether compounds, cyclic ether compounds, carboxylate compounds, sulfone compounds, and nitrile compounds; Preferably, the organic solvent is selected from any one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, 1,4-butyrolactone, ethyl methyl carbonate, methyl propionate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, dimethyl ether, benzene sulfide, acetonitrile, glutaronitrile and sulfolane; Furthermore, it is preferred that the organic solvent is a combination of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and the mass ratio of the ethylene carbonate, the dimethyl carbonate and the ethyl methyl carbonate is 15-25:35-45:35-45.
9. The electrolyte according to any one of claims 1 to 8, characterized in that The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium tetrafluoroborate, lithium perchlorate, lithium nitrate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium bis(pentafluoroethylsulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorosulfonylimide), lithium difluoro(bis(oxalato)phosphate and lithium tetrafluoro(oxalato)phosphate; Preferably, the lithium salt is lithium hexafluorophosphate.
10. A lithium-ion battery comprising a positive electrode sheet, an electrolyte, a separator and a silicon-carbon negative electrode sheet, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte for lithium battery with silicon cathode and lithium battery with silicon cathode
CN103594730A
A lithium ion battery having good cyclic effects and an electrolyte thereof
CN107293789A
Negative pole piece and lithium ion battery comprising same
CN113851655A
Silicon-based lithium ion battery electrolyte and battery thereof
CN116632347A
Ternary high-nickel lithium ion battery non-aqueous electrolyte and lithium ion battery
CN116936926A